2016
DOI: 10.12957/reuerj.2016.7095
|View full text |Cite
|
Sign up to set email alerts
|

Mapeamento dos erros de medicação em um hospital universitário [Mapping of medication errors at a university hospital] [Asignación de errores de medicación en un hospital universitario]

Abstract: RESUMO Objetivo: identificar os erros de medicação de um hospital universitário, classificando-os segundo a causa raiz e analisar suas principais causas. Método: estudo quantitativo descritivo retrospectivo, desenvolvido em hospital universitário no interior do estado de São Paulo. Amostra de 339 erros de medicação ocorridos no ano de 2010. Os dados foram coletados em março de 2011 por meio dos Relatórios de Não Conformidade. Resultados: a principal falha de segurança ocorreu na etapa de dispensação (40,4%) e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 10 publications
0
6
0
6
Order By: Relevance
“…Given the complexity of the medication system, errors can occur in the prescription, distribution, preparation and/or administration of medications, and even in patient monitoring (6) . Studies have shown the recurring insecurity to which patients are exposed (7)(8) . The scarcity of information on the subject in the scientific literature and from drug manufacturers themselves, makes it difficult to decide on the appropriate behavior to be adopted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the complexity of the medication system, errors can occur in the prescription, distribution, preparation and/or administration of medications, and even in patient monitoring (6) . Studies have shown the recurring insecurity to which patients are exposed (7)(8) . The scarcity of information on the subject in the scientific literature and from drug manufacturers themselves, makes it difficult to decide on the appropriate behavior to be adopted.…”
Section: Introductionmentioning
confidence: 99%
“…In medical prescription, the use of illegible letter, incomprehensible abbreviations, and the lack of standardization of the names and doses of medications are concerning factors. Drug dispensing at doses other than those prescribed is also a contributing factor to the occurrence of error in drug administration (8)(9) . However, in most cases, it is in the final stage of the medication process that the error not detected in previous steps is attributed exclusively to the nursing team.…”
Section: Introductionmentioning
confidence: 99%
“…Another relevant fact in this scientific production 17 is that mmost errors related to lack of the right medication, which reinforces the importance of appropriate pharmaceutical assistance, ensuring that the patient is receiving the right medication, in the adequate route and pharmaceutical form, in appropriate doses and correct times, through activities related to the analysis of prescription and administration final conference, which corroborates the findings of another study 13 that shows that, in this problematic, nursing represents the final professional of the process.…”
Section: Resultsmentioning
confidence: 96%
“…14 Another reason that influences errors and AE, in addition to work overload, is the lack of physical structure, as explained in the Pakistani international panorama 16 , which converged with the results of this study, and demonstrated solutions to the problem, pointing out the need to invest in the improvement of the physical structure of PHS and to increase the nursing team, in order to reduce the work overload, converging, therefore, with this study, and with another synthesis of knowledge. 15 Another reality 17 , which mapped medication errors from a large private HS, located in the countryside of São Paulo, Brazil, based on 339 notification reports of errors and AE resulting from nursing assistance, showed convergence of the same study state and divergence of the hospital institution ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…O uso de medicamentos no âmbito hospitalar é tão crítico quanto essencial, sendo que as diversas fases que o tangem são potenciais fontes de erros. Entre elas, a dispensação é uma das fases mais frágeis, ocasionando prejuízos diretamente aos pacientes 4,5 .…”
Section: Introductionunclassified